Development of Emulsi (electronic module practicum articulate storyline 3) to Support Self-Regulated Learning of Students - Sadikin, Ali; Hardianti, Risa Dwita (Journal of Environmental and Science Education, 2021)
The aim of this research is to develop Emulsi (electronic module practicum articulate storyline 3) to support self-regulated learning (SRL) of students which is valid and effective. This research is research and development and the subjects of this study are students of class VIII F of SMP Negeri 1 Ungaran. Data collection techniques in this study used validation sheets, tests, and students self-assessment sheets in SRL. This research begins at the Emulsi design then validated by validators with details on the average results of material (85%), linguistics (95%), media (80%), pretest and posttest construct questions (75%) , syllabus (97% ), lesson plans (95%), students self-assessment sheets in SRL (87%), the rubric for the assessment of the practice report (76%). The results of student learning pretest scores (36.11%) posttest scores (100%) and final scores obtained from the average value of the practicum report and posttest scores (77.77%). The result of N-gain is 0.73 indicating high criteria. The results of the self-assessment score in SRL is 75% or 27 of 36 students. Based on the results of the study, it can be concluded that the Emulsi can be said to be valid and effective to support the SRL of students.